Enteric nematodes and the path to up-regulation of type 2 cytokines IL-4 and IL-13. Issue 1 (September 2015) - Shea-Donohue, Terez; Sun, Rex; Bohl, Jennifer A.; McLean, Leon P.; Zhao, Aiping
Highlights Nematode-derived products are important for evasion of host defenses. Worm products have therapeutic potential. STAT6-dependent gene transcription changes gut function to promote worm expulsion.